The Political Economy of Reconciliation: A Theoretical Primer - Atin Basuchoudhary; Andreas Freytag (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Conflicts end. Often though, the roots of future conflict remain in fertile soil. The process of reconciliation among erstwhile enemies may be a way to deter future conflagrations; we have witnessed a number of examples such as in Rwanda or South Africa. However, to be sustainable and effective, this process may require cultural change. We use evolutionary game theory to model this process of cultural change. We postulate three cultures in a population – Conciliatory, Non-conciliatory, and Reciprocative. We then use the replicator dynamic to identify evolutionary stable outcomes. People in our population are boundedly rational. They may, therefore, “belong” to a particular culture. However, they learn to adopt other cultures if it is beneficial. We find first that people can learn to be Non-conciliatory even when Conciliation provides very real benefits. However, a population can learn the reciprocative culture to facilitate reconciliation. Whether it does or not depends on the initial distribution of the population among the three cultures and how people feel about the future. These results are well known in the Evolutionary Game Theory literature. However, to our knowledge, this is the first time these results have been applied to provide insights into post-conflict reconciliation processes.
Keywords: D78; H12; 330; conflict; reconciliation